A country road, a tree - Baker, Jo (London, England : Black Swan, 2015)
"From the best-selling author of Longbourn, a stunning new novel that follows an unnamed writer--Samuel Beckett--whose life and extraordinary literary gift are permanently shaped in the forge of war. When war breaks out in Europe in 1939, a young, unknown writer journeys from his home in neutral Ireland to conflict-ridden Paris and is drawn into the maelstrom. With him we experience the hardships yet stubborn vibrancy at the heart of Europe during the Nazis' rise to power; his friendships with James Joyce and other luminaries; his quietly passionate devotion to the Frenchwoman who will become his lifelong companion; his secret work for the French Resistance and narrow escapes from the Gestapo; his flight from occupied Paris to the countryside; and the rubble of his life after liberation. And through it all we are witness to workings of a uniquely brilliant mind struggling to create a language that will express his experience of this shattered world. Here is a remarkable story of survival and determination, and a portrait of the extremes of human experience alchemized into timeless art"
"This is a Borzoi book."
Keywords: Authors, Irish -- 20th century -- Fiction; Beckett, Samuel -- 1906-1989 -- Fiction; World War, 1939-1945 -- France -- Paris -- Fiction